Self sufficiency in the fishery sub-sector: challenges and prospects in Lagos State - Evbuomwan, Grace et al.; Sere-Ejembi, A. A.; Momah, A. P.; Sodipo, J. A.; Bada, A. A. (Abuja: Central bank of Nigeria, 2006)
The publication examines fish production in Lagos State of Nigeria. It covers production of fish from deep sea trawling; artisanal sources; development of aquaculture in the ecological zones; challenges and prospects of fish production in Lagos State.
Includes bibliographical references.
lje 9/9/13
Loans
Keywords: Agriculture-Nigeria; Fish Production